Mechanically robust, self-healing and conductive rubber with dual dynamic interactions of hydrogen bonds and borate ester bonds. (5th April 2022) - Zhang, Jiahao; Cao, Liming; Chen, Yukun
Graphical abstract: Highlights: Mechanically robust, self-healing and conductive composites were prepared. Supramolecular interaction and B(OH)4 − –catechol interaction achieved crosslinking for ENR. Dynamic reversible hydrogen bonds and borate ester bonds were introduced to endow composites excellent self-healing behavior. The frame network structure formed by CMCS and CNTs fillers reinforced the composites and rendered them with excellent electrical conductivity. Based on the satisfactory mechanical properties and electrical conductivity, the composites exhibited potential application value in strain sensors. Abstract: Recently, conductive polymers have attracted attention due to their potential in flexible electronic devices. However, the fragility of the matrixes limits their wide applications. Herein, we designed a rubber-based composite with robust mechanical properties, excellent conductive and self-healing performance. The composite was fabricated by a simple and maneuverable method via emulsion blending of epoxidized natural rubber (ENR), carboxymethyl chitosan (CMCS), dopamine (DA) and multi-walled carbon nanotubes (CNTs). By taking advantage of the synergistic effect between the dynamic reversible hydrogen bonds and borate ester bonds, the composite exhibited efficient self-healing behavior under moderate conditions. What's more, CMCS and CNTs were selectively dispersed in the matrix to construct a frame network structure, which increased the tensile strength to 3.61 MPa, and achieved the maximum conductivity of 6.64 × 10 −2 S/m. Furthermore, based on the stretchability and electrical conductibility, the composite is sensitively capable of capturing the variation of strain, and thus shows great potential in strain sensors.